Allah yang Mati: Sebuah Kajian Soteriologis atas Paradoks Kematian Yesus Kristus - Yustinus Yustinus (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Jesus' death on the cross presents a paradox between God's eternal nature and the reality of a dying God, sparking intense debate in pluralistic societies. This study analyzes the relationship between Jesus' divinity and death from a soteriological perspective using systematic theology and historical-biblical analysis. The research demonstrates that the doctrines of communicatio idiomatum and Chalcedonian Christology resolve this paradox by maintaining the integrity of both natures in one Divine Person of Jesus. The findings reveal that Jesus' death in human nature constitutes the ultimate expression of God's saving love. Precisely because Jesus is God, His sacrifice is able to redeem all humanity, while His humanity enables this redemptive event to occur. These findings not only strengthen the theological foundation of redemption doctrine but also provide a relevant resolutive framework for contemporary dialectics about Christ's identity. The theological implications require the church to embody cruciform spirituality through practices of kenosis and solidarity with the suffering.